Synthesis of new cyano‐substituted analogues of Tröger's bases from bromo‐derivatives. A stereochemical dependence of long‐range (nJHH, n = 4, 5, and 6) proton–proton and proton–carbon (nJCH, n = 1, 2, 3, 4, and 5) coupling constants of these compounds. (13th May 2019) - Dusso, Diego; Ramirez, Cristina; Parise, Alejandro; Lanza, P.; Vera, D. Mariano; Chesta, Carlos; Moyano, E. Laura; Akhmedov, Novruz G.
Abstract: A free‐catalyst microwave‐assisted cyanation of brominated Tröger's base derivatives (2a ‐f ) is reported. The procedure is simple, efficient, and clean affording the nitrile compounds (3a ‐e, I ) in very good yields. Complete assignment of 1 H and 13 C chemical shifts of2a ‐f, I and3a ‐d, I was achieved using gradient selected 1D nuclear magnetic resonance (NMR) techniques (1D zTOCSY, PSYCHE, DPFGSE NOE, and DEPT), homonuclear 2D NMR techniques (gCOSY and zTOCSY), and heteronuclear 2D NMR techniques (gHSQCAD/or pure‐shift gHSQCAD, gHMBCAD, bsHSQCNOESY, and gHSQCAD‐TOCSY) with adiabatic pulses. Determination of the long‐range proton–proton coupling constants n J HH ( n  = 4, 5, 6) was accomplished by simultaneous irradiation of two protons at appropriate power levels. In turn, determined coupling constants were tested by an iterative simulation program by calculating the 1 H NMR spectrum and comparing it to the experimental spectrum. The excitation‐sculptured indirect‐detection experiment (EXSIDE) and 1 H‐ 15 N CIGARAD‐HMBC (constant time inverse‐detection gradient accordion rescaled heteronuclear multiple bond correlation) were applied for determination of long‐range carbon–proton coupling constants n J CH ( n  = 2, 3, and 4) and for assignment of 15 N chemical shift at natural abundance, respectively. DFT/B3LYP optimization studies were performed in order to determine the geometry of2c using 6‐31G(d, p), 6‐311G(d, p), and 6–311 + G(d, p) basis sets. For calculation of 1 H and 13 C chemical shifts, n J HH (n = 2, 3, 4, 5, and 6), and n J CH ( n  = 1, 2, 3, and 4) coupling constants, the GIAO method was employed at the B3LYP/6‐31G(d, p), B3LYP/6‐31+G(d, p), B3LYP/6‐311+G(d, p), B3LYP/6‐311++G(2d, 2p), B3LYP/cc‐pVTZ), and B3LYP/aug‐cc‐pVTZ) levels of theory. For the first time, a stereochemical dependence magnitude of the long‐range n J HH ( n  = 4, 5, and 6) and n J CH (n = 1, 2, 3, 4, and 5) have been found in bromo‐substituted analogues of Tröger's bases. Abstract : Complete assignment of 1 H and 13 C chemical shifts of bromo and cyano derivatives of Tröger's bases was achieved using gradient selected 1D nuclear magnetic resonanceNMR techniques (1D zTOCSY, PSYCHE DPFGSE NOE, and DEPT), homonuclear 2D NMR techniques (gCOSY and zTOCSY), and heteronuclear 2D NMR techniques (gHSQCAD/or pure‐shift gHSQCAD, gHMBCAD, bsHSQCNOESY, and gHSQCAD‐TOCSY) with adiabetic pulses. Determination of the long‐range proton–proton coupling constants nJHH ( N  = 4, 5, 6) was accomplished by simultaneous irradiation of two proton frequencies. The 1 H 13 C EXSIDE and 1 H 15 N CIGARAD‐HMBC were applied for determination of long‐range carbon–proton coupling constants m J CH ( n  = 2, 3, and 4) and for assignment of 15 N chemical shift at natural abundance, respectively.